From instable directional switching to controlled unidirectional operation in a nonlinear fiber ring laser - Alexander Hartung; Muhammad Assad Arshad; Matthias Jäger (Scientific Reports, 2024)
Abstract We investigate a new phenomenon, where a reciprocal fiber ring laser switches from bidirectional to unidirectional operation above a certain pump power threshold. Significant simplifications regarding earlier experiments are presented, which for the first time allow the identification of individual nonlinear effects. We highlight the unique role of stimulated Raman scattering in triggering unidirectional operation, and that additional conditions apply. The threshold is reduced from 30 to 3.8 W, which eases potential applications.